The convention of a doctoral thesis in applied linguistics from a European and North American perspective - Canh, Lê Văn; Barnard, Roger (VNU Journal of Foreign Studies, 2012)
Abstract.This article provide guidance on how to write a good PhD thesis in Applied Linguistics according to the conventions and requirements commonly adopted by European and North American universities. The purpose of the article is to provide a reference for both PhD candidates and examiners in Vietnam in an attempt to narrow the gap between Vietnam-based PhD programmes and those offered by European and North American universities.Key words: applied linguistics, doctoral thesis, conventional structure, European and North American conventions.